G protein-coupled receptor-mediated renal fibrosis: a key focus on kidney disease drug development - Wang, Hui; Yang, Mengfan; Liu, Xiongfeng; Fan, Junming; Wang, Can (Frontiers in Pharmacology, 2025)
Renal fibrosis (RF) represents the pathognomonic end-stage phenotype of progressive nephropathies, pathologically characterized by excessive deposition of fibrillar extracellular matrix (ECM) and irreversible obliteration of parenchymal architecture. G protein-coupled receptors (GPCRs)—members of the heptahelical transmembrane receptor superfamily—function as master regulators orchestrating both physiological renal homeostasis and maladaptive fibrotic reprogramming in response to injury. Despite robust clinical evidence validating the therapeutic tractability of GPCR-targeted interventions for chronic kidney disease (CKD), no approved agents specifically antagonize the core pathogenic drivers of RF. Consequently, this review systematically delineates GPCRs exhibiting mechanistic primacy in RF pathobiology and translational promise, with focused interrogation of endothelin receptors, angiotensin receptors, chemokine receptors, and adenosine receptors. Beyond canonical modulation of inflammatory leukocyte infiltration and pro-fibrotic phenotypic transitions, emerging paradigms highlight GPCR governance over metabolomic reprogramming and mechanotransductive signaling during fibrogenesis. Notwithstanding these mechanistic advances, clinical translation of GPCR-directed anti-fibrotic therapeutics remains nascent, constrained by target pleiotropy, biodistribution barriers, and species-divergent pathophysiology. Collectively, GPCRs constitute high-value molecular targets for intercepting the progression of RF at its mechanistic nexus.